What is known about Peutz–Jeghers syndrome (a literature review) - M. H. Melnychenko; E. S. Buriachkivskyi; L. B. Eliy (Zaporožskij Medicinskij Žurnal)
Peutz–Jeghers syndrome (PJS) is an autosomal dominant disease, which in most cases is caused by mutation of the tumor suppressor gene STK11 and is characterized by the development of hamartomatous polyps in the digestive tract and the presence of hyperpigmented spots on the skin and mucous membranes. Late diagnosis of PJS leads to acute intestinal obstruction or bleeding.